Modern Understanding of Internal Financial Control: Problems and Perspectives of Investigation - S. R. Dreving; L. Y. Khrustova (Управленческие науки, 2016)
The analytical review of national and foreign approaches to the internal financial control is presented in this paper. The examination of existing approaches enabled to define the internal financial control as one of the management spheres within the economic entity, which provides the efficient achievement of goals and is realized by constructing a system of interrelated elements. Nevertheless the key moments of the notion specification are its aims and objectives, which vary depending on the nature of business, its scale and the levels of internal financial control realization. The authors’ understanding of demarcation of different financial control designations was noted as one of the conclusions. For instance, it seems necessary to divide such determinations as internal and corporate control as far as the corporate control category covers only some of the objects of internal financial control that limits the scope of its use. The article also touches upon the demarcation between the concepts of financial control, controlling, and internal audit. The authors determine the internal financial control as one of the key areas of practical implementation of controlling tasks and objectives. According to the hierarchy of concepts presented in the article, internal audit serves as the main tool of internal financial control. The emerging role of system and value-based approach, the necessity of industry and structure characteristics consideration during the process of internal financial control system development, the introduction of a new perspective direction of strategy financial control are pointed out as the main tendencies of internal financial control investigation. The undertaken analysis of existing approaches allowed forming a strong theoretical basis for the examination of practical aspects of internal financial control development and determining the key directions of the investigation.